Самый бешеный роман - Богданова Анна Владимировна (Такая смешная любовь, 2007)
Экземпляры: ф.12 (ретро) / Инвентарный номер: 44493 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 73 / ББК: 84(2Рос=Рус)6-4